Utilisation of Geothermal Energy that Impact Rights to Clean Water Needs - Adam Muhammad Yanis; Erina Pane (Fiat Justisia: Jurnal Ilmu Hukum, 2019)
Geothermal utilisation policy based on the consideration highlights that geothermal resources are natural resources which are low cost and environmentally friendly. In some countries, including in Indonesia, waste from geothermal utilisation causes pollution of water sources in geothermal working areas. A normative juridical method was employed in this study, which data was processed based on the research of secondary data. The study results indicated that (1) geothermal management in the protected forest area of Mount Slamet, Central Java in Indonesia, resulted in contamination of clean water sources that were commonly used by the community for their daily needs. The liquid that came out of the process of geothermal exploitation had an impact on water governance in protected forest areas. In some countries pollution of water sources caused a long-term threat to human health and environmental sustainability, (2) the danger of sustainability of water resources in protected forest areas, it was caused by the policies undertaken did not pay attention to the principle of prudence. Therefore, it is necessary to reformulate policies in the utilisation of geothermal resources.